Non-invasive detection and monitoring of oral squamous cell carcinoma and oral potentially malignant disorders: an umbrella review on diagnostic accuracy - M. C. C. Groenevelt; L. Meulenbroeks; R. H. Brakenhoff; J. B. Poell; M. P. Fransen; A. H. Zwinderman; E. R. Brouns; L. W. P. Peute (Clinical Oral Investigations, 2026)
Abstract Objectives Various non-invasive diagnostic techniques have been developed and assessed to improve early detection and monitoring of oral squamous cell carcinoma and oral potentially malignant disorders. However, a clear overview of the diagnostic performance and their ability to detect clinically relevant changes, is lacking. This study evaluated clinically tested, non-invasive techniques for early detection and monitoring of oral squamous cell carcinoma and potentially malignant disorders, focusing on diagnostic accuracy. Methods After a structured search strategy and critical selection of all relevant systematic reviews, data was extracted from 57 reviews in total, of which 29 were included for qualitative analysis, 20 for meta-analysis and eight for both qualitative and meta-analysis. Results Among nine techniques that are available in practice, optical coherence tomography, spectroscopy, and cytology with oral brushes demonstrated the highest effectiveness. Optical coherence tomography demonstrated the highest diagnostic accuracy, with a sensitivity and specificity estimated at 0.91 and a diagnostic odds ratio of 108.5. Furthermore, when combined with artificial intelligence, diagnostic accuracy is even further improved. Conclusions Most studies evaluating diagnostic accuracy of non-invasive diagnostic tests for potentially malignant disorders and oral squamous cell carcinoma grouped these conditions together without stratifying by lesion type. Therefore, no firm conclusions can be made about the diagnostic accuracy in detecting oral squamous cell carcinoma or different types of potentially malignant disorders. More high quality, primary studies should be conducted to specifically assess the diagnostic accuracy of different diagnostic tests per lesion type. Clinical relevance No clinical guidelines are currently available for management of oral potentially malignant disorders, and practical guidelines for clinical decision making in the field of oral squamous cell carcinoma and oral potentially malignant disorders will be helpful. The results of this umbrella review can inform clinical practice, guideline development, and future research priorities.